The leukemogenic potential of an enhancer variant of Moloney murine leukemia virus varies with the route of inoculation. - Belli, B (1994)
We previously showed that the Mo+PyF101 variant of Moloney murine leukemia virus (M-MuLV) is poorly leukemogenic when inoculated subcutaneously (s.c.) into neonatal mice. We recently found that intraperitoneal (i.p.) inoculation of neonatal mice with the same virus significantly enhanced its leukemogenicity. In this study, infections of neonatal mice by the two different routes of inoculation were compared. We studied replication of the virus in vivo to identify critical preleukemic events. These would be observed in mice inoculated i.p. by Mo+PyF101 M-MuLV but not when inoculation was s.c. Infectious center assays indicated that regardless of the route of inoculation, Mo+PyF101 M-MuLV showed delayed infection of the thymus compared with wild-type M-MuLV. On the other hand, i.p.-inoculated mice showed more rapid appearance of infectious centers in the bone marrow than did s.c.-inoculated animals. Thus, the enhanced leukemogenicity of i.p. inoculation correlated with efficient early infection of the bone marrow and not with early infection of the thymus. These results suggest a role for bone marrow infection for efficient leukemogenesis in Mo+PyF101 M-MuLV-infected mice. Consistent with this notion, if bone marrow infection was decreased by injecting 10- to 12-day-old animals i.p., leukemogenicity resembled that of s.c. inoculation. Thus, two cell types that are critical for the induction of efficient leukemia were implicated. One cell delivers virus from the site of s.c. inoculation (the skin) to the bone marrow and is apparently restricted for Mo+PyF101 M-MuLV replication. The second cell is in the bone marrow, and its early infection is required for efficient leukemogenesis.